(s+1)(4s-8)=0

Simple and best practice solution for (s+1)(4s-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (s+1)(4s-8)=0 equation:


Simplifying
(s + 1)(4s + -8) = 0

Reorder the terms:
(1 + s)(4s + -8) = 0

Reorder the terms:
(1 + s)(-8 + 4s) = 0

Multiply (1 + s) * (-8 + 4s)
(1(-8 + 4s) + s(-8 + 4s)) = 0
((-8 * 1 + 4s * 1) + s(-8 + 4s)) = 0
((-8 + 4s) + s(-8 + 4s)) = 0
(-8 + 4s + (-8 * s + 4s * s)) = 0
(-8 + 4s + (-8s + 4s2)) = 0

Combine like terms: 4s + -8s = -4s
(-8 + -4s + 4s2) = 0

Solving
-8 + -4s + 4s2 = 0

Solving for variable 's'.

Factor out the Greatest Common Factor (GCF), '4'.
4(-2 + -1s + s2) = 0

Factor a trinomial.
4((-1 + -1s)(2 + -1s)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-1 + -1s)' equal to zero and attempt to solve: Simplifying -1 + -1s = 0 Solving -1 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1s = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1s = 0 + 1 -1s = 0 + 1 Combine like terms: 0 + 1 = 1 -1s = 1 Divide each side by '-1'. s = -1 Simplifying s = -1

Subproblem 2

Set the factor '(2 + -1s)' equal to zero and attempt to solve: Simplifying 2 + -1s = 0 Solving 2 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1s = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1s = 0 + -2 -1s = 0 + -2 Combine like terms: 0 + -2 = -2 -1s = -2 Divide each side by '-1'. s = 2 Simplifying s = 2

Solution

s = {-1, 2}

See similar equations:

| (s+1)(4s-8)=0 | | 3x+2-2x+5=0 | | 2x-7x+21=26 | | 4x-18=7x+6 | | 9n-35=3n-9 | | (6m-7)(2m+12)=0 | | 3x+52-21=14 | | 7+65x=39x+19 | | 0.5Q-p=0 | | x+(x+1)+(x+2)=2(x+2)+1 | | (3h-7)(5h+4)=0 | | 3x+3=45x-81 | | (4k-2)(3k+6)=0 | | 0.2x+5.4=2x | | (m+11)(m-9)=0 | | 7(k-3)=k-5 | | (k+4)(3k-12)=0 | | (2x-1)*(5x+72)=250 | | (p-5)(p+2)=0 | | (p-5)(p+2)=0 | | 16t^2-49=0 | | b^2+7b+4=0 | | 5m+2=24 | | 4k=9 | | 3x+59-21=14 | | 318=10x | | 2x+y=xy | | (4y-8)(3y+7)=0 | | 100x+100=200 | | 100x-100x=212 | | 8x^3-12x^2-18x+17=0 | | 5+6x=56 |

Equations solver categories